2020
DOI: 10.7759/cureus.10216
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of the Evaluation and Assessment of the Etiology and Patterns of Ocular Injuries in Midfacial Trauma in a Tertiary Care Hospital

Abstract: The aim is to study the pattern of ocular injuries in midfacial trauma and to evaluate the overall incidence of ophthalmic injury of any severity following maxillofacial trauma. Methods and Materials The maxillofacial surgeon conducted routine facial examination of patients with midfacial fractures, which also included a detailed ophthalmologic examination of patients, at the time of initial presentation. These patients were then further evaluated by an ophthalmologist for thorough examination of the eye. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…It is therefore possible that a significant number of eye injuries could be prevented or avoided. However, any effort geared towards increasing PED use compliance should take into consideration the specific social and occupational features of the residents of that region [ 31 ], as the occupational characteristics of each region’s population are very important in determining the major sources of ocular injury in that area [ 1 , 9 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is therefore possible that a significant number of eye injuries could be prevented or avoided. However, any effort geared towards increasing PED use compliance should take into consideration the specific social and occupational features of the residents of that region [ 31 ], as the occupational characteristics of each region’s population are very important in determining the major sources of ocular injury in that area [ 1 , 9 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ophthalmic traumas include injuries of the eyelids, corneal and conjunctival abrasion, contusion of the globe, rupture, intraocular hemorrhage, optic nerve and orbital trauma, and retinal or chorio-retinal trauma [ 1 ]. According to Birmingham Eye Trauma Terminology (BETT), ophthalmic trauma can be classified into Open and Closed globe injuries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Midface fracture incidence and trauma patterns vary across countries, due to socioeconomic, environmental, and cultural factors. [ 2 3 4 5 6 ] In a study conducted in Nepal, midface fractures were reported to primarily occur in orbital floor (22.3%) and zygoma (21.5%), followed by zygomatic arch (7.6%), nasal bone (7.0%), supraorbital (4.2%), LeFort I (2.1%), LeFort II (2.2%), and LeFort III (1.5%). [ 5 ] According to Al Ahmed et al .…”
Section: Introductionmentioning
confidence: 99%